2008
DOI: 10.1002/anie.200705240
|View full text |Cite
|
Sign up to set email alerts
|

A Near‐Infrared‐Fluorescence‐Quenched Gold‐Nanoparticle Imaging Probe for In Vivo Drug Screening and Protease Activity Determination

Abstract: Nanodiagnosis: A matrix‐metalloproteinase (MMP) sensitive gold‐nanoparticle (AuNP) imaging probe quenches conjugated near‐infrared (NIR) dyes with high efficiency and is specifically activated by the target MMPs (see picture, left). With this system, nanomolar amounts of protease can be detected—both in vitro and in vivo. Experiments disclose an apparent positive contrast in MMPs‐positive tumor‐bearing mice (right).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
132
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 311 publications
(132 citation statements)
references
References 26 publications
(3 reference statements)
0
132
0
Order By: Relevance
“…A nearinfrared-fluorescence (NIRF)-quenched gold-nanoparticle imaging probe for in vivo drug screening and protease activity determination has been reported by Lee et al [44]. The probe is used to sense matrix metalloprotease (MMP) activity or their inhibitors which are mainly involved in cancer, inflammation and vascular disease.…”
Section: In Vivo Tumor Imagingmentioning
confidence: 99%
“…A nearinfrared-fluorescence (NIRF)-quenched gold-nanoparticle imaging probe for in vivo drug screening and protease activity determination has been reported by Lee et al [44]. The probe is used to sense matrix metalloprotease (MMP) activity or their inhibitors which are mainly involved in cancer, inflammation and vascular disease.…”
Section: In Vivo Tumor Imagingmentioning
confidence: 99%
“…The limitations of FRET can be overcome with a dynamic molecular method based on the distance-dependent plasmon coupling of metal nanoparticles. Recently several groups including ours [14,[18][19][20][21][22][23][24][25][26][27][28][35][36][37][38][39][40][41] have reported that nanoparticle surface-energy transfer (NSET) is a technique capable of measuring distances nearly twice as far as FRET in which energy transfer from a donor molecule to a nanoparticle surface follows a predictable distance dependence. Like FRET, [44,45] the interaction for NSET is dipole-dipole in nature, but is geometrically different beAbstract: We report size-and distancedependent surface-energy transfer (SET) properties of gold nanoparticles for recognizing hepatitis C virus (HCV) RNA sequence sensitively and selectively (single-base mutations) in a homogeneous format.…”
Section: Introductionmentioning
confidence: 99%
“…For the control group, MMP inhibitor III (EMD Biosciences), a broad-spectrum inhibitor of various MMPs, was injected into the tumor 30 min prior to the probe injection. [23] As shown in Figure 3, without MMP inhibitor the probes demonstrated an instant response upon injection, and the activity developed steadily in the first 2 hours. On the contrary, the control group showed dramatically decreased intensities at the tumor area at all the time points, thus confirming that the activation was specifically governed by MMPs.…”
mentioning
confidence: 88%
“…[12][13][14][15] Such an implication has made MMP a good tumor marker and a common target in the design of activatable probes. [16][17][18][19] We and others have previously developed activatable probes, based on either peptide, [16,19,20] polymer, [17,21,22] or inorganic nanoparticles, [23,24] of MMP targeting specificity. On the other hand, the use of protein as a building block to construct MMP-activatable probes has, to the best of our knowledge, never been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation